The value pedestrians attribute to environmental information diminishes in route choice sequences. (March 2021) - Tong, Yunhe; Bode, Nikolai W.F.
Graphical abstract: Highlights: Pedestrians attend less to information the more route choices they make in sequence. The effect can be formalised in a flexible mathematical model for route choice. Implication 1: usage of a signposted shortest route may decrease in egress. Implication 2: following may be suppressed making crowd egress more predictable. Abstract: Suppose someone wants to walk from one location to another location. In doing so, they either follow a pre-planned route or decide which way to go each time they reach a junction. Research into pedestrian dynamics has carefully studied route planning and single instances of decisions on routes. However, little is known about the decision-making processes in sequences of consecutive pedestrian route choices. Here, we propose the first mathematical model for this situation. Its key hypothesis is that the sensitivity of pedestrians to environmental information, such as signs or the movement of others, diminishes, the more decisions they make in sequence. To validate our model, we conduct a virtual reality experiment with over 200 participants. Our findings suggest that sensitivity to information diminishes for the experimental case when only information on the movement of others is available to pedestrians. Comparison of our model to situations when signs are present and to data from previously published work suggests that this effect cannot be detected in short sequences of route decisions that contain three or fewer decision points. We demonstrate the implications of this diminishing sensitivity to environmental information at the example of egress from a metro-station. While the proportion of pedestrians using a signposted shortest route may decrease, following behaviour is also suppressed which may result in more predictable route choice dynamics across pedestrian crowds. We advocate further study on this topic in real-world settings, to investigate the need for appropriate pedestrian route choice management strategies. Our experiment also provides preliminary insights into how different personality traits affect following behaviour and we suggest this opens another avenue for future investigation.